Clinical outcome of curettage in atypical cartilaginous tumors of the long bones: a descriptive cohort study - Claire H J Scholte; Michiel A J van de Sande; Robert J P van der Wal; Demien Broekhuis; Kirsten van Langevelde; Desirée M J Dorleijn (Acta Orthopaedica)
Background and purpose: Despite evolving management strategies for atypical cartilaginous tumors (ACT)—shifting from radical resection to intralesional curettage and “wait-and-scan” approaches—there remains no universal consensus on optimal treatment. We primarily aimed to evaluate disease-specific and progression-free survival following intralesional curettage and adjuvant phenol treatment of ACTs. Secondary aims included assessing surgical complications, the need for additional interventions, and an overview of long-term follow-up. Methods: This retrospective cohort study of 388 ACT patients was conducted at a tertiary referral center from 2000 to 2019. Comprehensive data collection included demographics, tumor characteristics, and follow-up outcomes. Results: Residual disease was observed in 14% (n = 53) of cases, with continued growth on sequential imaging in one-fourth (n = 13 of 53). Postoperative fractures occurred in 10% (n = 37) after a mean of 7 months, and 16% (n = 61) required a second surgery due to pain or joint movement limitations. There was no malignant progression or mortality observed. Conclusion: We found that curettage for ACT is not associated with mortality or malignant progression but does carry risks of complications and residual disease. This raises important questions regarding the necessity of surgical intervention. Further research is needed to refine the treatment approach for ACT.